The Prevalence of Gastrointestinal Parasites and Seroprevalence of Toxoplasma gondii in Captive Ocelots (Leopardus pardalis) in Trinidad, West Indies. (27th May 2021) - Bally, Alissa; Francis-Charles, Stacy; Ackbar, Tariq; Beharrylal, Yadel; Charles, Roxanne; Basu, Asoke; Suepaul, Rod
Abstract : This study was conducted from November 2010 to June 2011 to determine the prevalence of gastrointestinal parasites and the seroprevalence of Toxoplasma gondii in captive ocelots ( Leopardus pardalis ) in Trinidad. Faecal samples were collected and analyzed using faecal flotation to identify helminth ova and protozoan cysts and oocysts. Serum samples from captive ocelots were screened for T. gondii using a latex agglutination test kit. Of the 19 ocelots examined, the most prevalent parasites noted were ova of ascarids, strongyles, and Capillaria spp. The serum of three of the 13 (23.1%) ocelots tested was positive for T. gondii antibodies. These ocelots are therefore a potential source of T. gondii infection to both humans and other animals. This is the first documented report of endoparasites in local captive ocelots within Trinidad and provides useful data to support further research of the captive and wild populations.